LEGITIMASI HEGEMONI HUKUM ADAT DALAM KARYA SASTRA BERLATAR KULTURAL BALI - Dwipayana, I Kadek Adhi; Adnyana, Ida Bagus Gede Bawa (JURNAL ILMU BUDAYA, 2019)
AbstractThis article talks about the legitimacy of Balinese customary law and the reinterpretation of the authors of Balinese customary law in cultural literary works. Theoretically, this research has an urgency in the development of science, especially the knowledge of literary discourse, while practically providing understanding to the public about Balinese customary law and how to address the cultural problems of the people in Bali. This study used a descriptive qualitative research design that moved from a functional approach to Balinese cultural literary works. The primary data sources of this research are a collection of "Bunga Jepun" short stories by Fajar Arcana, "Mandi Api" by Aryantha Soethama, Novel "Tarian Bumi" by Oka Rusmini, and "Incest" by Wayan Artika. The research data were collected by the library study method and then analyzed based on a qualitative descriptive approach. The results of the study indicate that the legality of Balinese customary law is questioned in cultural literary works on marital customary law, inheritance law, neglect law, and the law of malik sumpah.